Incoordination during the pharyngeal phase in severe dysphagia due to lateral medullary syndrome. Issue 3 (9th February 2021) - Kunieda, Kenjiro; Sugi, Takafumi; Ohno, Tomohisa; Nomoto, Akiko; Shigematsu, Takashi; Kanazawa, Hideaki; Fujishima, Ichiro
Abstract: One of the mechanisms of severe dysphagia due to lateral medullary syndrome may be a reversed pressure gradient caused by incoordination of pharyngeal contractility and UES opening during swallowing. Abstract : One of the mechanisms of severe dysphagia due to lateral medullary syndrome may be a reversed pressure gradient caused by incoordination of pharyngeal contractility and UES opening during swallowing.